Simulation of the chromatographic separation process in HPLC employing suspended‐state NMR spectroscopy – comparison of interaction behavior for monomeric and hydride‐modified C18 stationary phases. Issue 1 (29th November 2012) - Yeman, Helen; Nicholson, Tim; Matyska, Maria T.; Pesek, Joseph J.; Albert, Klaus; Svec, Frantisek
<x xml:space="preserve">Abstract</x> The interactions of different analytes with monomeric and hydride‐modified stationary phases have been investigated employing suspended‐state NMR spectroscopy. The suspended‐state high‐resolution/magic‐angle‐spinning 1H‐NMR spectrum of an analyte in the presence of C18 SP material shows a splitting into two sets of signals for the analyte molecule. One state reflects a closer interaction between analyte and C18‐modified surface that results in an upfield shift and broader signal half‐widths. This phenomenon suggests that the analyte exists in two environments. We report a systematic approach upon the investigation on the interaction in the interface of analyte, mobile phase, and modified silica through synthesis of differently modified silica with a gradual increase in surface coverage. The determination of the signal half‐widths and chemical shifts revealed a relationship between the modification technique of the C18 SPs and the chromatographic and NMR spectroscopic behavior. Increasing ligand density results in higher shielding of the NMR signals for the analyte in the "adsorbed" state. The measurement of spin‐lattice relaxation times T1 of the analyte molecule correlate NMR parameter together with separation behavior in HPLC. Furthermore, suspended‐state and solid‐state NMR measurements revealed different alkyl chain mobilities for the monomeric and hydride‐modified SPs.